2017
DOI: 10.1111/jgh.13816
|View full text |Cite
|
Sign up to set email alerts
|

Muscular thickness of lower esophageal sphincter and therapeutic outcomes in achalasia: A prospective study using high‐frequency endoscopic ultrasound

Abstract: Thickening of the outer longitudinal muscle at the lower esophageal sphincter is associated with poor mid-term treatment outcomes for achalasia patients treated with pneumatic dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(56 reference statements)
1
7
1
Order By: Relevance
“…In the 30 years since these studies, the number of studies that use different EUS techniques and include more participants have increased. Our results agree with many of these studies, where most of the individuals in the present study had a thickened LEMP[ 5 - 7 ]. This suggests that LEMP thickness may be of value in achalasia diagnosis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the 30 years since these studies, the number of studies that use different EUS techniques and include more participants have increased. Our results agree with many of these studies, where most of the individuals in the present study had a thickened LEMP[ 5 - 7 ]. This suggests that LEMP thickness may be of value in achalasia diagnosis.…”
Section: Discussionsupporting
confidence: 94%
“…While its etiology remains uncertain, achalasia is characterized by the destruction of inhibitory ganglion cells in the myenteric plexus, causing severe myopathy in smooth muscles and leading to aperistalsis and impaired relaxation of the lower esophageal sphincter (LES)[ 1 , 2 ]. In addition, thickened lower esophageal muscularis propria (LEMP) has been observed in individuals with achalasia in vivo and during autopsies[ 3 - 7 ]. LEMP hypertrophy may be a response to esophageal functional obstruction or a primary lesion[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rigiflex dilator is the commonly used dilator with a fully inflated diameter that usually ranges from 3 cm or more to achieve maximal pressure for a satisfactory result. Dilations can be performed by either a fluoroscopy-guided procedure [12, 13, 26] or endoscopy-guided procedure [9, 14]. Dilation sessions and the inflation time needed for a successful dilation vary between patients and are operator dependent.…”
Section: Treatment Evolution: From Conventional Treatment To Perormentioning
confidence: 99%
“…Esophageal muscle layer thickness was identified as the most important clinical factor affecting duration of POEM procedures. As for mid- and long-term outcomes of POEM, a few studies have suggested that a thick preoperative esophageal muscle layer might be a predictor of failure of PD 7 . Patients whose esophageal muscle layers were < 1.3 mm thick exhibited a significantly higher mid-term success rate after PD than those with thicker esophageal muscle layers (100 % vs. 36.3 %, P = 0.01).…”
Section: Introductionmentioning
confidence: 99%